Temporal and spatial behavior of pharmaceuticals in Narragansett Bay, Rhode Island, United States. (31st January 2017) - Cantwell, Mark G.; Katz, David R.; Sullivan, Julia C.; Ho, Kay; Burgess, Robert M.
Abstract: The behavior and fate of pharmaceutical ingredients in coastal marine ecosystems are not well understood. To address this, the spatial and temporal distribution of 15 high‐volume pharmaceuticals were measured over a 1‐yr period in Narragansett Bay (RI, USA) to elucidate factors and processes regulating their concentration and distribution. Dissolved concentrations ranged from below detection to 313 ng/L, with 4 pharmaceuticals present at all sites and sampling periods. Eight pharmaceuticals were present in suspended particulate material, ranging in concentration from below detection to 44 ng/g. Partitioning coefficients were determined for some pharmaceuticals, with their range and variability remaining relatively constant throughout the study. Normalization to organic carbon content provided no benefit, indicating other factors played a greater role in regulating partitioning behavior. Within the upper bay, the continuous influx of wastewater treatment plant effluents resulted in sustained, elevated levels of pharmaceuticals. A pharmaceutical concentration gradient was apparent from this zone to the mouth of the bay. For most of the pharmaceuticals, there was a strong relationship with salinity, indicating conservative behavior within the estuary. Short flushing times in Narragansett Bay coupled with pharmaceuticals' presence overwhelmingly in the dissolved phase indicate that most pharmaceuticals will be diluted and transported out of the estuary, with only trace amounts of several compounds sequestered in sediments. The present study identifies factors controlling the temporal and spatial dynamics of dissolved and particulate pharmaceuticals; their partitioning behavior provides an increased understanding of their fate, including bioavailability in an urban estuary. Environ Toxicol Chem 2017;36:1846–1855. Published 2016 Wiley Periodicals Inc. on behalf of SETAC. This article is a US government work and, as such, is in the public domain in the United States of America.